Interrogating Michel Foucault's Counter-Conduct: Theorising the Subjects and Practices of Resistance in Global Politics. Issue 2 (2nd April 2016) - Odysseos, Louiza; Death, Carl; Malmvig, Helle
Abstract : Resistance, and its study, is on the rise: visible and politically discernible practices of dissent against sovereignty and economic exploitation, such as protesting, agitating and occupying, have received increased analytical attention in the past decade. This special issue provides much needed systematic attention to less visible practices of resistance or those not manifested in expressly political registers. It focuses on attempts to inventively modify, resist or escape the ways in which we are governed by interrogating critically the politics and ethics of resistance to "power that conducts", expressed through Foucault's notion of "counter-conduct". The contributions first theoretically interrogate, develop and refine the concept of "counter-conduct(s)", offering a major statement of its importance for both the study of resistance and also its place in Foucault's work. Second, they provide inter/multi-disciplinary empirical investigations of counter-conduct in numerous thematic areas and spaces of global politics. Third, they explicitly reflect on variable and contingent forms of counter-conduct, examining its close relationship with conducting power. Finally, the special issue concertedly considers issues of methodology and method emerging from the study of counter-conduct and how these also recalibrate the study of governing power itself.